Dynamic characteristics of micro-perforated complex beam structures - The, Vu Van (Edelweiss Applied Science and Technology, 2024)
This paper discusses research concerning the fluctuating dynamic characteristics of various micro-beams featuring intricate designs and perforated surfaces across their entire operational faces. The complex beam structures consist of different types: folded beam, V-shaped beam, and crab-shaped beam with different boundary conditions: fixed-free, fixed-fixed for the simple single beam, and fixed-guided for the rest. The types of holes on the body of the beams are choice in square and circle-shaped for common. In addition, the methodology to determine the dynamic characteristics of the perforated beam is also proposed based on using FEM simulation software. The results show that the dynamic characteristics of the beam in which the holes are distributed depend on the size and shape of perforated holes. As the size or quantity of holes on the surface of the beam in perforated micro-beams grows, the equivalent stiffness drops noticeably. Consequently, the fundamental frequencies of the MEMS systems that include these micro-beams also diminish. The damping coefficient also reduces thanks to the occurrence of these holes. The maximum decrease in damping coefficient reaches 84% in the ideal case for the crab-shaped beam with square holes. These results can be used to optimize the MEMS structures in future research.